Documents and democracy: How classification shapes public confidence in democratic institutions - Sarah Maxey; Taryn Butler (Research & Politics)
Access to and control over the classification process is a key component of executive power in the United States. This power is rooted in the public’s trust that the White House will safeguard national secrets and use its authority to protect national security. Secrecy, however, is in tension with democratic norms of transparency, making political backlash possible if leaders stretch their powers too far. What are the consequences of mishandled documents for the public’s trust in the government? We argue that the abuse of classified documents undermines not only presidential approval but also confidence in democratic institutions writ large. We test these expectations using survey experiments that vary information about the type of document classified, whether the White House handled top secret documents correctly, and evidence of mishandling by either civilian or military officials. The findings show that while the public generally tolerates secrecy and executive power, the consequences when the White House breaks this trust are wide-ranging and undermine public confidence in democracy as a whole.